A Comparison of Musculoskeletal Disorders of Neck and Shoulder Girdle in Male Computer Users with and without Physical Activity - farhad nikravan golsefidi; Ahmad Ebrahimi Atri; Ali Akbar Hashemi Javaheri (Sport Sciences and Health Research)
The present study aimed at investigating musculoskeletal condition of neck and shoulder girdle in active and inactive male employees who worked with computers. 120 male employees were selected by cluster sampling method and divided into two groups (first group with physical activity and second group without physical activity). Their musculoskeletal condition of their neck and shoulder girdle were assessed by Nordic standard questionnaire. This study was descriptive, correlational-comparative with an application nature. The collected data were analyzed by SPSS21 and descriptive statistics and Chi Square test (α≤0.05). Results showed a significant difference in musculoskeletal condition of neck and shoulder girdle between the two groups (P=0.001) and the group with physical activity enjoyed a better condition. As physical activity and fitness may decrease musculoskeletal disorders, training and regular physical activities can affect the prevention of musculoskeletal disorders of neck and shoulder girdle and can prevent enormous costs.